Christ's Pistis vs. Caesar's Fides Pistis Christou in Galatians and the Roman Imperial Cult - Lee, Sang Mok (2019)
This study examines the meaning of πίστις Χριστοῦ with respect to the political and religious situations of Paul’s Galatian recipients, including the issue of circumcision. When the apostle sent his letter to the Galatian churches, the Gentile believers were returning to the Roman imperial cult; by doing so, they were accepting the emperor as the ultimate authority and benefactor and incorporated into the reciprocity of fides. Through πίστις Χριστοῦ, our apostle criticised and superseded this Roman imperial ideology and the imperial cult. Paul’s πίστις Χριστοῦ was intended to advocate Christ’s faithfulness in opposition to Caesar’s faithfulness. He exhorted the recipients to live in a relationship of πίστις with Christ, not Caesar. Christ’s faithfulness and ‘the believer’s faith in Christ’ are not mutually exclusive. Paul deliberately intended the ambivalence of the Greek phrase to denote the reciprocal πίστις between Christ and the believer. The apostle defined the believer’s relationship with both the Jewish tradition and the Roman Empire concurrently.
Keywords: Galatians; Faithfulness; Fides; imperial cult; imperial ideology; Pistis; Pistis Christou; Reciprocity